Comparing the effectiveness of phrase-focused exercises: A partial replication of Boers, Demecheleer, Coxhead, and Webb (2014). (May 2017) - Boers, Frank; Dang, Tu Cam Thi; Strong, Brian
In a recent article, Boers, Demecheleer, Coxhead, and Webb (2014) deplored the lack of effectiveness for the learning of verb–noun collocations of a number of exercise formats which they sampled from EFL textbooks and put to the test in a series of quasi-experimental trials. The authors called for further investigations into possible improvements to such exercise formats. The present article is a response to that call. It also addresses methodological issues that may have affected Boers et al.'s (2014) findings and that rendered their conclusions tentative. In the quasi-experiment reported here, EFL learners were given fill-in-the-blank exercises on verb–noun phrases in one of three formats: (1) choose the appropriate verb, (2) complete the verb by using a first-letter cue, and (3) choose the appropriate intact phrase. A delayed post-test gauged the learners' ability to recall the meaning of the phrases as well as their verb–noun partnership. In both regards the exercise where learners worked with intact phrases generated the best results. We then evaluate the extent to which exercises for phrase learning in 10 recent EFL textbooks accord with recommendations that follow from the quasi-experimental findings.